Hubungan Sanitasi Lingkungan Keluarga dengan Kejadian Stunting pada Balita: The Relationship of Environmental Sanitation with Stunting Events of Toddlers - Tia Feronika Asi H Iman; Lensi Natalia Tambunan; Eva Prilelli Baringbing (Jurnal Surya Medika (JSM), 2022)
Background: Stunting or short infants are chronic nutritional problems marked by inappropriate height compared with age. Environmental sanitation affects a stunting event in toddlers, with poor access and toilet facilities, lack of waste and waste management facilities, lack of access to clean hands and food as well as cleaning utensils, a risk of diarrhea and disability in the family in the result of the outbreak of viruses, germs, and bacteria. Research Objectives: Research was done to identify the sanitation of the family environment with stunting events. Research Methods: The research design used is a literature review, using the design study case-control and cross-sectional, using base data that is Google scholar and the garuda portal, and using the reference year of 2019-2021. Results: a study of 6 articles shows that environmental sanitation (the type of toilet, waste removal, domestic wastewater disposal, drinking, food consumption, and water resources) is associated with stunting events in toddlers. Conclusion: environmental sanitation is linked to stunting events in toddlers. Households that lack availability of clean water and inappropriate water treatment before use can cause nutritional problems in children. Since watering with a coliform bacteria content exceeds the threshold of raw water sources, it can cause a variety of stomach ailments if not properly treated. A history of diarrhea in the last three months may be risky for stunting events in infants